FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI BEKASI - Siti Aisyah; Rutji Satwiko (E-Jurnal Akuntansi TSM, 2022)
Tax is one source of income for a country. The purpose of this research is to get empirical evidence about the effect of taxpayer awareness, moral obligations, quality of services, tax sanctions, tax understanding and knowledge and tax socialization on vehicle’s taxpayer compliance at Bekasi. The theory used in this research is Attribution Theory and Theory of Planned Behavior. The respondent's criteria used in this study are motor vehicle taxpayers who are registered at the Bekasi SAMSAT and self payments of vehicle’s tax. This research design uses a questionnaire as an instrument. Sampling in this study was conducted as many as 115 motor vehicle’s taxpayers who have passed the criteria. The sampling method used was convenience sampling. The results of the analysis and hypothesis testing showed that simultaneously or partially there are 3 variables that affect taxpayer compliance. 1. Taxpayer awareness, The effect of Taxpayer awareness on Taxpayer compliance because the higher the level of awareness of Taxpayers who have understood well how the benefits of paying taxes and the implementation of tax obligations are getting better. 2. Tax sanctions, the effect of tax sanctions is due to strict and consistent enforcement of tax laws in the country with respect to the sanctions given, it will be able to create high compliance because taxpayers have understood well what penalties or sanctions will be obtained if they do not pay their taxes. 3. Socialization of taxation is influential because the tax authorities often carry out tax socialization, taxpayers often see advertisements or explanations about taxation either through print media or the internet and understand the information provided by the tax authorities so that taxpayers increase information or understanding of taxation, so that socialization is carried out carried out by the tax authorities have been effective and on target.